Advanced Ceramic Processing 2015
DOI: 10.5772/61026
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Fast Sintering of Double Perovskite Ceramic Materials

Abstract: The book chapter mainly deals with the microwave sintering of high quality crystals of La MMnO M = Ni or Co ceramics. Double perovskite La MMnO M = Ni or Co ceramics with average particle size of ~ nm were manufactured using microwave sintering at °C for min in N atmosphere for the first time. The morphology, structure, composition, and magnetic properties of the prepared compacts were characterized using X-ray diffraction XRD , scanning electron microscopy SEM , transmission electron microscopy TEM , energy-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
3
0
2
Order By: Relevance
“…Double perovskite La 2 MMnO 6 (M = Ni, Co) was successfully prepared by Matli et al using the microwave sintering technique. The obtained material exhibited improved magnetic and dielectric properties with a reduced sintering time in comparison to conventionally obtained products [21].…”
Section: Application Of Microwave Sintering In the Fabrication Of Different Engineering Materialsmentioning
confidence: 92%
“…Double perovskite La 2 MMnO 6 (M = Ni, Co) was successfully prepared by Matli et al using the microwave sintering technique. The obtained material exhibited improved magnetic and dielectric properties with a reduced sintering time in comparison to conventionally obtained products [21].…”
Section: Application Of Microwave Sintering In the Fabrication Of Different Engineering Materialsmentioning
confidence: 92%
“…Figure 1 a,b depicts the differences in the working principles of the CS ( Figure 1 a) and MWS ( Figure 1 b) methods, demonstrating that conventional sintering has a slower heating rate than microwave sintering. When compared to CS, microwave sintering offers the following advantages: (i) volumetric and uniform heating, (ii) faster sintering resulting in reduced sintering time, (iii) better temperature control, (iv) improved properties, and (v) minimum energy consumption [ 6 , 7 ]. A survey revealed that iron ore powder is sintered at a high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…gives rise to 180° ferromagnetic interactions between Ni 2+ (d 8 ,S=1) and Mn 4+ (d 3 , S=3/2) ions governed by Kanamori-Goodenough rules [17]. Recent studies show the microwave sintering effect on properties of La2NiMnO6 [18], effect of A site (Ba) substitution effect on structural, magnetic and vibrational properties of La2NiMnO6 double perovskite [19,20,21], effect on electric and dielectric properties of B site (Mg) doping on La2NiMnO6 [22], high transition temperature and short ferromagnetic ordering in La2FeMnO6 [23]. The substituted La2NiMnO6 composition properties were engineered to make it potential candidate for applications.…”
Section: Introductionmentioning
confidence: 99%